Pharmacognostic and phytochemical studies as an invaluable approach for correct identification of medicinal plants: The case of Artemisia vulgaris L. substituted for Artemisia annua L. in Western Uganda - Kahwa, Ivan; Chauhan, Nagendra Singh; Omara, Timothy; Asiimwe, John Baptist; Ikiriza, Hilda; Anke, Weisheit; Ogwang, Patrick Engeu (TMR Integrative Medicine, 2023)
Different parts of Artemisia vulgaris L. (A. vulgaris) are ethno-medicinally used as an emmenagogue and for the treatment of ailments such as malaria fever, ulcers, and cancer. However, anecdotal evidence shows that the plant is often substituted for Artemisia annua L. (A. annua) by herbalists in Western Uganda due to similarities in their morphology. Misidentification of medicinal plants and mislabelling of herbal products have been incriminated in toxicity and adverse health outcomes in traditional medicine practise. Because safety continues to be a major issue with the use of herbal remedies, it becomes imperative therefore that medicinal plants should be correctly identified. Methods: This study focused on investigating the macroscopic, microscopic, physicochemical characteristics and phytochemical composition of A. vulgaris leaves compared to A. annua to ease its correct identification. Results: The results showed that there are some colour differences between the leaves of the two species, with a close arrangement of microscopic features but different leaf constants. The leaves of the two Artemisia species had similar tastes, but their shapes and colours (greenish-yellow for A. annua and dark green for A. vulgaris) can be used by the local community to distinguish between them. The artemisinin content was higher in A. vulgaris leaves (1.72 %) than in A. annua (1.43%), but the reverse was observed for the total flavonoid content. Conclusion: This observation could justify the change in the use of A. vulgaris by the indigenous community in western Uganda. Further studies should consider the pharmacognostic comparison of A. annua with other species in the genus Artemisia and the use of molecular techniques such as DNA barcoding.